2021
DOI: 10.3390/jmse9030295
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Narrowing Barrier Islands along the Coast of Pakistan over Past 30 Years

Abstract: Barrier islands (BIs) are the first line of defense against the sea/wave actions in coastal areas, and assessing their stability is crucial in the context of effective coastal planning. Therefore, this study evaluates the spatial–temporal shoreline changes of the BIs in Pakistan over the past three decades (1989–2018). Satellite data from Landsat missions are used to delineate the shorelines of 19 BIs in Pakistan. After delineating the shorelines from satellite observations, two well-known statistical methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Erosion in the East Karachi sub-zone suggests that these natural barriers gaurding against the erosional effects coming from the Arabian Sea have already been badly impacted. This finding is broadly in accord with the earlier work of Kanwal, et al [13], which also found that the islands were undergoing very high erosion (~8.9 m/yr). However, more assessment in this regard is required-this is left for future work.…”
Section: Influence Of Ground Displacement On Coastal Erosion In Karachisupporting
confidence: 92%
See 2 more Smart Citations
“…Erosion in the East Karachi sub-zone suggests that these natural barriers gaurding against the erosional effects coming from the Arabian Sea have already been badly impacted. This finding is broadly in accord with the earlier work of Kanwal, et al [13], which also found that the islands were undergoing very high erosion (~8.9 m/yr). However, more assessment in this regard is required-this is left for future work.…”
Section: Influence Of Ground Displacement On Coastal Erosion In Karachisupporting
confidence: 92%
“…This reduction in the sediment supply has escalated the erosional effects of tides and waves, resulting in seawater intrusion (SWI) into coastal plains. The results from these studies agreed well with those of Kanwal, et al [13], who investigated the evolution of the barrier islands (BIs) along Sindh coastal regions in Pakistan and concluded that ~65% of these BIs underwent high erosion (i.e., >2 m/yr), during 1989-2018. Their study implies that the ~15% of these BIs experiencing moderate erosion (i.e., <2 m/yr), are likely to be subjected to high erosion (i.e., >2 m/yr) in the wake of SLR and reduced sediment influx received by the IDR plains in the near future, without proper measures.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Fluctuations in freshwater currents coming down from inland dams and irrigation also affect mangroves by altering their salinity and resulting in mangrove loss [262]. For instance, in Pakistan, the Indus Delta freshwater incurrent has been reduced by up to 90% due to diversion [263]. This affected the bed load composition and reduced the uniform sediment deposition in those mangrove areas [264].…”
Section: Altered Hydrological Flowmentioning
confidence: 99%
“…Traditional field surveys have certain limitations in terms of their monitoring scope, frequency, and intensity [16]. Combining remote sensing (RS) with geographic information system (GIS) technology, coastal landforms have been effectively monitored in near real time at different spatial scales and resolutions [17][18][19][20][21][22][23]. Murray et al (2019) mapped the global tidal flats during 1984-2016 using Landsat images [11].…”
Section: Introductionmentioning
confidence: 99%